TEKNIK PICTURE AND PICTURE DALAM PEMBELAJARAN MENULIS TEKS PROSEDUR KOMPLEKS - Ardisa Nadilestari (Sekolah Pascasarjana Universitas Pendidikan Indonesia, 2016)
This research is motivated by a student's difficulties in expressing ideas when writing text complex procedures. Text is the text of the complex procedures that are new in the curriculum of 2013. The research objective tobe achieved is to determine the extent of the student's ability to write text complex procedures, as well as the effectiveness of the use of picture and picture techniques in teaching writing. Picture and picture technique ie, students are given a picture that has been randomized to the topic of learning. Then the students put the image into a logical order and write down the main idea of each image with the help of teachers, so that students can make the text complex procedures sequentially. The results obtained from this study is that there is a significant difference average value of post-test experimental class and control class. The value of the average post-test experimental class is 80.69 was the value of